Genet ic Variat ion and Diversity Analysis of Chickpea Genotypes based on Quant itat ive Traits under High Temperature Stress - Jha, Uday Chand; Basu, Parthasarathi; Singh, Deepak (International Journal of Bio-resource and Stress Management, 2023)
Sixty two chickpea genotypes were investigated to capture the existing genetic variability for heat stress tolerance. Genotypes revealed significant wide genetic variation for eight different quantitative and morpho-physiological traits. Considering phenotypic coefficient of variation (PCV) and genotypic coefficient of variation (GCV), membrane stability trait exhibited highest PCV (64.75%) and GCV (56.3%). While, highest broad sense heritability (h2B) was recorded for membrane stability (75%), followed by pods/plant (53%) and days to maturity (46%). Importantly, positive correlation between days to 50% flowering and plant height, pods/plant and plant height, pods /plant and membrane stability were recorded. Similarly, days to maturity and membrane stability showed high positive correlation. Cluster analysis based on the given 8 traits grouped all the 62 genotypes into eight distinct clusters. Cluster 2 and 8 contained 12 genotypes each. The first three principal components of 8 traits contributed 60.8% of the total existing variability present in the given genotypes. Most important traits contributing diversity in PC1 were days to maturity and membrane stability, where as, pods/plant and plant height in PC2 and plot yield and leaf area index (LAI) in PC3. Additionally, the following two genotypes Katila (232.5 gm), Vaibhav (222.5 gm) were showed higher plot yield than check ICC92944 (heat stress tolerant) (192.5 gm) under heat stress. Results from the given study would be useful for to design heat stress tolerant improved chickpea cultivar.